Impact of fertilizer use on production and cash income of small-scale farmers in the highland areas of Ethiopia - Belete, A.; Dillon, John L.; Anderson, F.M. (Elsevier, 1992)
Farmer's use of fertilizer in the highland areas of Ethiopia remains small, despite significant yield increases obtained in experimental stations and on-farm trials. Among the suspected hindrances against the use of fertilizer at the rate recommended jointly by the MOA/IAR, are farmers' aversion for risk and shortage of credit to purchase fertilizer. This paper evaluates the impact of fertilizer use on incomes of small-scale farmers in the highland areas of Ethiopia, and the risk associated with fertilizer use, using a MOTAD risk programming model. The results show that if farmers apply fertilizers at the recommended rate of 100 kg of DAP and 50 kg of urea, their production, and hence cash income, will improve substantially. However, this improvement in cash income is at the expense of higher risk associated with cash income when fertilizer is used. This is true, particularly for one of the study areas, Ada sub-district.